Aquatic animal health programmes : their benefits for global food security (World Organisation for Animal Health ParisFR, 2012)
Provides an overview of the available knowledge on aquatic animal health and its contribution to ensuring global food security. Includes recommendations.
Keywords: ANIMAL HEALTH